Absence of effects of prolonged simvastatin therapy on nocturnal sleep in a large randomized placebo-controlled study. Oxford Cholesterol Study Group. - Keech, A; Armitage, J; Wallendszus, K; Lawson, A; Hauer, A; Parish, S; Collins, R (1996)
1. It has been suggested that lipophilic HMG CoA reductase inhibitors, like lovastatin and simvastatin, may cause sleep disturbance. 2. Six hundred and twenty-one patients at increased risk of coronary heart disease were randomized in a single centre to receive 40 mg daily simvastatin, 20 mg daily simvastatin or matching placebo. To assess the effects of prolonged use of simvastatin on nocturnal sleep quality and duration, a sleep questionnaire was administered to 567 patients (95% of 595 survivors) at an average of 88 weeks (range: 44-129 weeks) after randomization. 3. The main outcome measures were sleep-related problems and use of sleep-enhancing medications reported during routine study follow-up visits, and responses to the sleep questionnaire about changes in sleep duration and about various sleep events during the preceding month. 4. No differences were observed between the treatment groups in the frequency of sleep-related problems reported, in the proportion of follow-up visits at which such problems were reported, or in the use of sleep-enhancing medications. The numbers who stopped study treatment were similar in the different treatment groups, and no patient stopped principally because of insomnia. In response to the sleep questionnaire, there were no significant differences between the treatment groups in reports of various sleep events during the preceding month, except that slightly fewer patients allocated simvastatin reported waking often. No differences in sleep duration were observed. 5. This placebo-controlled trial does not indicate any adverse effects of prolonged treatment with simvastatin on systematically sought measures of sleep disturbance.